PENYELESAIAN SENGKETA TANAH DI TIMOR LESTE OLEH DIRECÇÃO NACIONAL DE TERRAS, PRORIEDADES E SERVIÇOS CADASTRAIS (DNTPSC) DENGAN METODE MEDIASI BERDASARKAN LEI NU 1/2003 - Duarte da Silva; Seguito Monteiro; José Agostinho da Costa Belo Pereira (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
The problem of land disputes in Timor Leste is caused by a conflict between Article 54.4. which states that only national citizens have ownership rights to land and article 22 which states that, Timor Leste citizens who are or live abroad have the right to state protection in the exercise of their rights and will be subject to obligations that do not conflict with its absence in the country. Conflict creates a vacuum in norms so that disputes often occur over ownership of land rights. Timor Leste's National Land Agency, namely, Direcção Nacional de Terras, Propriedades e Serviços Cadastrais (DNTPSC) or the National Directorate of Land Services, Property and Cadastre, based on Article 17 of Law Number 1 of 2003 concerning Legal Regulations, has the authority to manage aspects land, such as land ownership rights for citizens as legal subjects, land management procedures, and institutions that handle land issues. In carrying out its duties relating to land and resolving land disputes, DNTPSC chooses a non-litigation resolution method, namely mediation. Article 2, Lei nu 1/2003 is the basis for the attribution of authority for the DNTPSC to carry out government duties in the land sector and resolve existing land disputes.